Регіональна політика vs просторові зрушення економіки України: пошук відповідей на актуальні питання - Кравців, В.С.; Сторонянська, І.З. (Вісник НАН України, 2025)
У статті визначено сучасні тренди та ризики просторових зрушень економіки України, обґрунтовано пріоритети державної регіональної політики в контексті відповідей на актуальні виклики. В умовах повномасштабної війни РФ проти України та окупації територій інструментарій регулювання просторового розвитку економіки виявився неефективним, що зумовлює необхідність переосмислення методології регіональної політики, її завдань та механізмів реалізації. Основними напрямами вдосконалення державної регіональної політики в контексті сучасних викликів визначено практичну імплементацію територіально орієнтованого підходу в практику управління розвитком регіонів та громад; удосконалення системи стратегічного та просторового планування розвитку територій України; формування інституційної системи використання коштів європейських фондів (зокрема, в межах реалізації програми Ukraine Facility); завершення реформування місцевого самоврядування і територіальної організації влади в Україні, зокрема організації публічної влади на регіональному та субрегіональному рівнях. The purpose of this article is to identify the current trends and risks associated with spatial shift s in Ukraine’s economy and to justify the priorities of state regional policy in addressing these emerging challenges. The spatial development model of Ukraine’s economy, inherited from the USSR, has led to interregional economic disintegration, the gradual exclusion of certain territories from the national economic space, and an intensification of regional confrontations. Amidst the Russian occupation of Ukrainian territories and the ongoing full-scale war, the existing toolkit for managing the spatial development of the economy has proven ineffective, necessitating a re-evaluation of regional policy methodologies, objectives, and implementation mechanisms. The article identifies primary areas for enhancing state regional policy in response to modern challenges: implementing a territorially-oriented approach to regional and community development management; improving the strategic and spatial planning system for Ukraine’s territories; developing an institutional framework for utilizing European funds (particularly within the framework of the Ukraine Facility program); and completing the reform of local self-government and the territorial organization of power in Ukraine, including the establishment of public authority at the regional and subregional levels.